2018
DOI: 10.2478/prolas-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds in Tomatoes at Different Stages of Maturity

Abstract: Tomato is known as a vegetable with several health benefits due to its high level of bioactive compounds, especially lycopene, phenolics, and vitamin C. The effect of tomato variety and stage of maturity on the bioactive compounds concentration was studied. Ten tomato varieties were grown and collected from a greenhouse at two different stages of ripening. The obtained results showed that there were significant differences in the mean values between analysed parameters according to the stage of ripening and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
4
11
0
Order By: Relevance
“…In our study, the concentration of lycopene in cherry tomatoes was considerably higher than that detected in big size tomatoes, regardless of tomato colour, but lower concentration was determined for yellow tomatoes. The results reported here are in line with previous studies (Markovic et al, 2006;Bojarska et al, 2020) in which lycopene concentration in fresh tomatoes ranged from 1.82 to 11.19 mg•100 g -1 wet weight; similar also to values reported by Asensio et al (2019) and Coyago-Cruz et al (2019) as well to our previous results (Dûma et al, 2018), but lower than those reported by Marti et al (2016). The lycopene concentration was on average 30% higher in red tomatoes than in brown tomatoes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the concentration of lycopene in cherry tomatoes was considerably higher than that detected in big size tomatoes, regardless of tomato colour, but lower concentration was determined for yellow tomatoes. The results reported here are in line with previous studies (Markovic et al, 2006;Bojarska et al, 2020) in which lycopene concentration in fresh tomatoes ranged from 1.82 to 11.19 mg•100 g -1 wet weight; similar also to values reported by Asensio et al (2019) and Coyago-Cruz et al (2019) as well to our previous results (Dûma et al, 2018), but lower than those reported by Marti et al (2016). The lycopene concentration was on average 30% higher in red tomatoes than in brown tomatoes.…”
Section: Discussionsupporting
confidence: 93%
“…It was concluded that small-fruited tomatoes have the highest concentration of phenolic compounds, especially in autumn, and the concentration is lower by ~5% in spring. The results reported here are in line with the data presented by Asensio et al (2019) and Alenazi et al (2020), and slightly lower than in other reports (Dûma et al, 2018;Bojarska et al, 2020). However, it should be noted that the comparison is often difficult due to the great influence of agronomic factors such as varieties, growing conditions and harvesting time.…”
Section: Discussionsupporting
confidence: 90%
“…Tomatoes are rich in vitamins like A, C, K, B6 and folate and thiamine and minerals like potassium, manganese, magnesium, phosphorus and copper. It also contains dietary fiber, protein and organic components such as lycopene, polyphenolic compounds and phenolic acid which are very important for human health (Bergougnoux 2014;Dūma et al, 2018). Due to the above mentioned features, tomato consumption continues to increase every year.…”
Section: Anahtar Kelimelermentioning
confidence: 99%
“…Mahmood et al [29] also stated that total flavonoids had increasing maturity in strawberry and mulberry from Pakistan. Moreover, Duma et al [33] described bioactive compounds of tomatoes at various ripening stages and observed the increase in total flavonoids as maturity developed.…”
Section: Btotal Flavonoid Contentmentioning
confidence: 99%